1997
DOI: 10.1111/j.1440-6055.1997.tb01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of RAPD PCR to Distinguish the B Biotype from Other Biotypes of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae)

Abstract: The use of RAPD PCR to identify the B biotype of the whitefly Bemisia tabaci and distinguish it from other biotypes and species of whitefly is described. The technique enables the use of alcohol preserved material instead of live or frozen material as required by allozyme electrophoresis and demonstrates that eggs, juvenile stages and males or females can all be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(196 citation statements)
references
References 8 publications
1
194
0
1
Order By: Relevance
“…DNA was extracted from 10 individual insects of each sample, according to a standard protocol (Barro and Driver, 1997) with several modifications. Individual female whiteflies were homogenized in 56 µl lysis buffer (10 mM TrisHCl, pH 8.0, 1 mM EDTA, 0.30% Triton X-100, 60 µg/ml proteinase K) using a 1.5-ml microcentrifuge tube and micropestle.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from 10 individual insects of each sample, according to a standard protocol (Barro and Driver, 1997) with several modifications. Individual female whiteflies were homogenized in 56 µl lysis buffer (10 mM TrisHCl, pH 8.0, 1 mM EDTA, 0.30% Triton X-100, 60 µg/ml proteinase K) using a 1.5-ml microcentrifuge tube and micropestle.…”
Section: Methodsmentioning
confidence: 99%
“…The technique enables the use of alcohol preserved material as required by allozyme electrophoresis and demonstrates that eggs, juvenile stages and males or females can be used (De Barro and Driver, 1997). Hajimorad et al, (1996) reported the presence of (ToLCV) the virus in tomato growing provinces of southern but not northern Iran.…”
Section: Biotypes Of B Tabacimentioning
confidence: 99%
“…This pest can cause damage through feeding, causing sooty mold by its honeydew, transmitting more than 111 species of plant-pathogenic viruses, and inducing plant physiological discords (Brown 1994;Heinz 1996;Jones 2003). The worldwide losses caused by this pest exceed $300 million annually (De Barro and Driver 1997;White 1998). The actual number of biotypes of this pest is unknown, but at least 24 different biotypes have been identified (Perring 2001), of which biotype B is the most serious and widely distributed one.…”
Section: Sweetpotatomentioning
confidence: 99%
“…Bemisia tabaci, especial biotype B, is difficult to control because of its high resistance to many insecticides available in the market, its wide range of hosts, and rapid rate of development and reproduction (De Barro and Driver 1997;He and Huang 2005). In China, the control of B. tabaci mainly relies on chemical insecticides, which has caused many serious problems .…”
Section: Sweetpotatomentioning
confidence: 99%